The Application of the Restraining Order Mechanism to Domestic Violence Crimes - Noer, Aleydha Patriana; Agustanti, Rosalia Dika (Universitas Semarang, 2024)
This article aims to analyze the legal protection for victims of domestic violence through the Restraining Order mechanism. In addition, this article also aims to provide recommendations for legal improvements so that the use of the Restraining Order mechanism can be more effective. In Indonesia, the mechanism of Restraining Order has not been regulated in detail in the law. Law No. 23/2004 on the Elimination of Domestic Violence has mentioned the existence of a protection order against victims that can be given by the police or the court, but this protection order is not well implemented. Therefore, the urgency of this article is to provide definitive protection to victims of domestic violence through the mechanism of Detention Orders. This article is a normative legal research. The novelty of this article is about analyzing the use of Restraining Order punishment in Common Law countries, as well as providing suggestions regarding the clarity of Restraining Order Implementation in Indonesia. The results of this study indicate that the Restraining Order mechanism used by Common Law countries is more effective in providing protection to victims of domestic violence because basically the legal protection of victims of domestic violence in Indonesia only relies on Law Number 23 Year 2004 which the contents of the Law are still not fully effective in protecting victims of domestic violence.